Clinical and morphological evaluation of the course of chronic periodontitis in patients with coronary heart disease - Mazur, I.; Yanishevskii, K. (Actual Dentistry, 2018)
Introduction. Periodontal diseases occupy one of the main places in the structure of oral morbidity. Recently, more and more attention to the influence of the cardiovascular pathology on the development periodontal disease was paid. Studies show a correlation between morphological changes in the aorta structure, in particular, the average thickness of aorta intima and changes in periodontal tissues. Aim: to determine clinical and morphological changes of periodontal tissues in patients with chronic periodontitis (ChP) and coronary heart disease (CHD). Materials and methods. The study was involved 190 patients with GP and CHD, which were divided into 4 groups. The 1 group consisted of 23 patients with an initial severity of GP, 2 group included 54 patients with mild ChP, 3 group included 87 patients with moderate ChP and the 4-th group included 26 patients with severe ChP. All patients were given a dental and periodontal examination with the definition of the index of oral hygiene, the papillary-marginal-alveolar index, measured the depth of periodontal pockets and the loss of clinical attachment level. Morphological studies were carried out on incisive biopsy specimens of the ascetic papillae. Results. The deterioration of the oral hygiene index was observed with increasing severity of the ChP, which constituted in patients in the 1, 2, 3 and 4-th groups 2.12±0.11; 2.32±0.11; 3.23±0.14 and 3.62±0.16 points, respectively. The increase of inflammation activity in periodontal tissues by the papillary-marinal-alveolar index in the groups was observed and constituted 34.12±1.43; 44.68±1.94; 76.60±2.10 and 77.54±2.12 % in the 1, 2, 3 and 4-th groups respectively. Morphological changes of periodontal tissues, characterized by uneven lesions of the epithelial layer, dystrophic altered velocity epithelium, focal alteration phenomena and necrotic changes in the gum tissue, disorders of the microcirculatory channel, narrowing of the lumen of the arterioles and widening of the venous vessels, were observed. Conclusion. Increasing of ChP severity is accompanied by a deterioration of oral hygiene and increasing inflammation in periodontal tissues. Increasing of ChP severity is accompanied by an increasing in the pathological process and morphological changes in the periodontal tissues due to the ischemic state of all tissues of the organism as a consequence of chronic cardiovascular insufficiency. Histological preparations of gum biopsy in patients with ischemic state are observed to increase the degenerative, necrobiotic and focal necrotic changes, which often lead to the destruction of epithelial cells and basement membrane and significant disorders of the microcirculatory channel. Key words: chronic periodontitis, coronary heart disease, morphology, morphological changes of periodontal tissues